ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK DAERAH SEBAGAI SUMBER PAD KOTA PONTIANAK (Studi Pada Badan Keuangan Daerah Kota Pontianak Tahun 2017-2021) - Pramesti, Ajeng; Ramadhannisa, Ifanka; Damayanti, Fera (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2023)
This research was conducted to examine the effectiveness and contribution of local taxes to local revenue (PAD) in Pontianak City. This research uses descriptive research. The source of the data to be obtained for this research is secondary data in the form of tables on the development of Pontianak City Regional Original Revenue Realization in 2017-2021. Data analysis techniques in this study used the effectiveness ratio analysis technique and contribution ratio analysis. The research results show that in 2017-2020 the level of effectiveness of regional tax revenues is quite effective, and the contribution of local taxes to Regional Original Revenue (PAD) for 2017-2021 is very good. The Regional Government of Pontianak City should continue to improve supervision, socialization and evaluation of local taxes so that local tax revenues achieve the tax target.